„Irlandia Północna – stąd pochodzę”: Glenn Patterson, powieściopisarz i obywatel w pogoni za „nieplemienną” tożsamością - Bartnik, Ryszard (Porównania, 2021)
Northern Ireland’s socio-political milieu over recent decades “pressured” its residents to affiliate with one of the two strongly antagonizing identities. In 1998, the Good Friday Agreement was signed to terminate the conflict between the Catholic/ Nationalist and Protestant/Unionist side. The primary aim of that settlement was to establish a solid collective framework for securing mutual coexistence, but more importantly it endorsed the idea of a regional (reformed) identity to be shared by both communities. And inasmuch as the aforementioned societal consensus has been institutionalized, even if only on the very rudimentary level, then bidding farewell to political/religious (almost sectarian) sympathies has turned to be far more difficult. Glenn Patterson stands among those home-grown writers who have been struggling with the burden of such troublesome identity formations. Therefore, the paper’s main focus is to explore the setbacks Patterson and the like face when trying to acknowledge a distinctly new character of Northern Irishness. In doing so, he highlights that the sine qua non of any potential success consists in deconstructing/defying the deep-seated divisions of the Troubles. Mindful of the journal’s thematic frame of a timely consideration of the “Recovered Territories,” I intend to depict Patterson as an individual/author/citizen whose artistic endeavor has been constantly gravitating towards reclaiming the ground for [re]building he Northern Irish identity, and replacing the well-known (Catholic-Protestant/ Irish-British) dichotomies. Drawing upon two collections of Patterson’s non-fiction accounts, Lapsed Protestant from 2006 and Here’s Me Here from 2016, my article concentrates upon both the hopes and obstacles manifested during the post-Troubles context of an attempted tropism towards a more neutral/non-politicized Northern Irish identification, in hopes that the similar dynamics may also shed light upon the Polish context.